Comperative Economic Analysis of the Determining Leagues of European Clubfootball - Bács, Bence András (International Journal of Engineering and Management Sciences, 2020)
Nowadays sport is not just all about entertainment, or about social cohesion but also it has serious economic and business aspects. Sporteconimics is an individual concept and sector. Sport businesses are contributing more and more to national incomes. Football business are specially important parts of this complex system called sporteconomics. The aim of my research is to create an economic and also comparative analysis of the five top European football leagues, also called as the “Big5” which are responsible for 74% of the total football revenue in Europe. By the analysis of the 2019 UEFA report it can be stated that in these leagues more than 60% of the competing clubs achieved positive operating profits, but the structure of their revenues warns them to look for opportunities to increase their operating revenues. According to the data it is clear that wage cost is the most significant cost element in the industry as they cover 53-68% of their total revenue. These statements set the course for the economic development of European football. The management of these outstanding football clubs may give example to the ones falling behind including Hungarian football businesses.